An Immortal Science : Alchemy's Role in Harry Potter and the Deathly Hallows - Angel, Will A. (East Carolina University, 2011)
I chose Hallows above any other novel in the series because it holds a stronger connection with alchemy than any of those before it. Hallows provides a density of alchemical symbols and imagery that far outshines any of its predecessors. In fact, Rowling introduces many new alchemical symbols into the series with Hallows, and I believe she "saves the best for last" in this respect. Hallows is unique because it functions as the Rubedo novel of the Harry Potter series while also serving as a representation of the complete alchemical cycle (Nigredo, Albedo, Rubedo) within itself. This capacity makes the alchemy in Hallows more pronounced than in earlier novels. Furthermore, Hallows is the first novel in the series to feature scripture from the Bible. With a Christian thread in the narrative, Hallows provides a means of exploration for the connection between a simultaneously alchemical and Christian narrative. Finally, Hallows centers much attention on the dynamic between Harry, Hermione, and Ron. I focus on this dynamic and pull from what Rowling says she may "never use in the books" to show how each character carries out his or her respective alchemical duties. In short, Hallows is the most concentrated example of Rowling's alchemical pen, and its place as the finale of her series cements it as the basis for my study.
Keywords: Literature; Christianity; Fantasy literature; Symbols; Harry Potter and the deathly hallows; Rowling, J. K. Harry Potter and the deathly hallows; Alchemy in literature; Potter, Harry (Fictitious character)